EP1003 Meigs' syndrome with elevated serum CA125: case report and review of the literature. (1st November 2019) - Tsaousidis, C; Walter, CB; Braendle, J; Oettling, C; Wallwiener, D; Brucker, SY
Abstract : Introduction/Background: The ovarian cancer represents the seventh most common cancer in women worldwide. An elevated serum CA 125 level in association with a pelvic mass, pleural effusion, and massive ascites usually signifies a dismal prognosis in a postmenopausal woman. Meigs' syndrome consists of a benign ovarian tumor accompanied by ascites and pleural effusion. Methodology: Surgery and histopathological examination are required for the correct diagnosis and treatment. The patient underwent a laparotomy with bilateral salpingo-oophorectomy. All cases of Meigs' syndrome with elevated CA 125 that have been reported were included at this review. Results: Meigs' syndrome with marked elevated CA 125 is a rare clinical entity and only 47 cases have been reported. An elevated CA 125 level can be falsely positive for ovarian malignancy because the quantity of ascites might be correlated with a rise in the level of CA 125. Conclusion: Postmenopausal women with a pelvic mass, pleural effusion, ascites and elevated serum CA 125 levels probably suffer from malignant ovarian tumors. However, it is important to remember that these findings does not always predict a lethal condition, but a benign adnexal lesion as part of Meigs' syndrome, should be also considered as an unusual but existing diagnostic possibility. Disclosure: Nothing to disclose.